$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# 6.9: Discontinuous Forcing

In the last section we looked at the Heaviside function its Laplace transform. Now we will use this tool to solve differential equations.

Example

A 1 kg bar is attached to a spring with spring constant 5 and damping constant 2. It is pulled down 3 inches from it equilibrium position and the released. After one second a constant force of 10 Newtons is exerted on the bar. The force remains turned on indefinitely.  Determine the equation of motion of the bar.

Solution

We have the differential equation

$y'' + 2y' + 5y = 10u_1(t)$

with

$y(0) = 3$

$y'(0) = 0$

We solve this by the method of Laplace transforms.  We have

$L\{y''\} + 2L\{y'\} + 5L\{y\} = 10L\{u_1(t)\}$

$s^2L\{y\} - 3s - 0 + 2(sL\{y\} - 3) + 5L\{y\} = 10e^{-s} /s$

$(s^2 + 2s + 5)L\{y\} - 3s - 6 = 10e^{-s} /s$

$L\{y\} = \dfrac{3s + 6 }{s^2 + 2s + 5} + \dfrac{10 }{s(s^2 + 2s + 5)}$

We use partial fractions on the second term

$\dfrac{10}{s(s^2 + 2s + 4)} = \dfrac{A}{s} + \dfrac{Bs+C}{s^2+2s+5}$

$A(s^2 + 2s + 5) + (Bs + C)s = 10$

$(A + B)s^2 + (2A + C)s + 5A = 10$

The constant term gives

$$A =2$$

Thus

$$B = -2$$        $$C = -4$$

We can complete the square

$s^2 + 2s + 5 = (s+1)^2 +4$

Putting all the algebra together we get

\begin{align} L\{y\} &= \dfrac{3s + 6}{(s + 1)^2 + 4} + e^{-s}\dfrac{2}{s} + e^{-s}\dfrac{-2s - 4}{ (s + 1)^2 + 4 } \\ &= 3\dfrac{s + 1 + 1}{(s + 1)^2 + 4} + e^{-s}\dfrac{2}{s} - 2e^{-s}\dfrac{(s + 1) + 1 }{(s + 1)^2 + 4 } \\ &= 3\dfrac{s + 1}{(s + 1)^2 + 4} + 3/2 \dfrac{2}{(s + 1)^2 + 4} + e^{-s}\dfrac{2}{s} - 2e^{-s}\dfrac{(s + 1) }{(s + 1)^2 + 4 } - e^{-s}\dfrac{2 }{(s + 1)^2 + 4 } \end{align}

Now use the table to take the inverse Laplace transform to get

$y = 3e^{-t}\cos(2t) + 3/2 e^{-t -1}\sin(2t) + 2u_1 - 2u_1(t)e^{-t +1}\cos(2t - 2) - u_1(t)e^{-t +1} \sin(2t - 2)$

Below is the graph